2019
DOI: 10.3390/ijerph16010141
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Workplace Injuries in Slovak Forest Enterprises

Abstract: The aim of the paper is to analyse the effect of key factors affecting the risk of workplace injuries and to identify the most common workplace accidents regarding injured body parts with respect to anthropometric data measurements of the population. Data associated with workplace accidents over the years 2000–2016 were drawn from the records of the state enterprise Forests of the Slovak Republic, situated in Banská Bystrica. Gathered data were processed and entered into the database complemented by the data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…However, employees can be motivated also by non-financial way more precisely by promotion or praise. The effort to create a good climate at workplace or the creation of a health and save work environment are also important (Gejdos et al, 2019;Naile & Selesho, 2014;Muogbo, 2013). At the same time, it is necessary to take into consideration the fact that every employee is different, has different needs and he is motivated by something else in every stage of his career advancement.…”
Section: Theoretical Developmentsmentioning
confidence: 99%
“…However, employees can be motivated also by non-financial way more precisely by promotion or praise. The effort to create a good climate at workplace or the creation of a health and save work environment are also important (Gejdos et al, 2019;Naile & Selesho, 2014;Muogbo, 2013). At the same time, it is necessary to take into consideration the fact that every employee is different, has different needs and he is motivated by something else in every stage of his career advancement.…”
Section: Theoretical Developmentsmentioning
confidence: 99%
“…Several studies have investigated the relationship between employment sectors and WRI and have identified employment sector as an important risk factor for the occurrence of fatal injuries in the workplaces [13,20,31,32]. In these studies, the agriculture, forestry, and fishing sector was found to be the leading industry in reporting fatal injuries among workers, followed by construction and mining sectors [23,25,[32][33][34]. When conveyance injuries were excluded in the current study, workers from information and technology; electricity, gas, and steam; wholesale and retail trade; and construction and building sectors demonstrated higher rates of fatal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The average accident rate in forestry in the years 2003-2017 amounted to 8.19 per 1000 employees, while for the country as a whole in 2017 the rate was 6.84 [26]. In turn, a study carried out in Slovakia for the period 2000-2016, where similarly to Poland the majority of forest operations are carried out by private companies, showed the absence of any significant drop in the accident rate in forestry [23].…”
Section: Discussionmentioning
confidence: 99%
“…The fatality rate was markedly higher in the private sector. The majority of fatal accidents take place during the timber harvesting process (e.g., [11,16,18,23,[29][30][31][32][33][34]). The privatization of forest operations in the State Forests Holding in Poland resulted in the transfer of virtually all of the most dangerous operations to the private sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation